Coding in scratch. Games workbook - Woodcock, Jon; Setford, Steve (DK Publishing, 2016)
"Computer coding is quickly becoming a necessary and sought after skill and schools have incorporated it into their curriculum, beginning as early as kindergarten to ensure students understand the languages and uses of computer coding. This workbook is full of fun exercises and step-by-step guidance, making it the perfect introductory practice book to build vital skills in one of the fastest growing industries"--Penguin Putnam.